2008
DOI: 10.3141/2067-06
|View full text |Cite
|
Sign up to set email alerts
|

Does Urban Road Pricing Cause Hardship to Low-Income Car Drivers?

Abstract: A major criticism of the principle of urban road pricing (also known as congestion charging and congestion pricing) is that it is regressive, namely, that the implementation of a charging scheme is likely to result in the imposition of a disproportionately large financial burden on low-income car users and their dependents, thereby resulting in hardship. A road pricing proposal in Edinburgh, Scotland, was used as a case study to assess the potential for road pricing-related hardship. Hardship occurs when peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Bonsall and Kelly, 2005;Crawford, 2000;Graham et al, 2009;Rajé, 2003;Santos and Rojey, 2004). Cain and Jones (2009), for example, looked at the likely consequences of a proposed two-cordon congestion charging scheme in Edinburgh on low income households, by applying the concept of 'hardship' that is widely used in the energy and water sectors; this results when a household spends more than a threshold percentage of their expenditure on a given sector. The study found that around 8.5% of Edinburgh households in the lowest income quintile (around 3500 households) could suffer hardship as a result of the introduction of the scheme.…”
Section: Finance-relatedmentioning
confidence: 99%
“…Bonsall and Kelly, 2005;Crawford, 2000;Graham et al, 2009;Rajé, 2003;Santos and Rojey, 2004). Cain and Jones (2009), for example, looked at the likely consequences of a proposed two-cordon congestion charging scheme in Edinburgh on low income households, by applying the concept of 'hardship' that is widely used in the energy and water sectors; this results when a household spends more than a threshold percentage of their expenditure on a given sector. The study found that around 8.5% of Edinburgh households in the lowest income quintile (around 3500 households) could suffer hardship as a result of the introduction of the scheme.…”
Section: Finance-relatedmentioning
confidence: 99%
“…Two studies conducted in Australia found that car-related costs sometimes exceed 40% of the income of households in the lowest income quintile [13,25]. Comparable figures were found for Scotland by Cain and Jones [10].…”
Section: Indicators Of Transport Poverty Risk and Accessibility Povermentioning
confidence: 53%
“…A higher share of overall household budget spent on transport expenditures suggests that household may be at risk of accessibility poverty, because they may not be able to maintain such a level of expenditures over a longer period of time or may experience problems in purchasing other necessities due to high transport expenditures. Some low-income car-owning households may also seek to control their transport expenses by minimizing car use, suggesting that car ownership does not necessarily translate into car-based accessibility under all circumstances [10]. The share of income spent on transport is thus an indicator pointing at households at risk of transport poverty, which may translate into a risk at accessibility poverty, as explained above.…”
Section: Indicators Of Transport Poverty Risk and Accessibility Povermentioning
confidence: 99%
See 1 more Smart Citation
“…Given this situation, car availability could be used as the prime criterion to divide the population into groups with high and lower levels of potential mobility. Furthermore, since potential mobility is also related to transport costs, an additional partitioning into income groups may supplement the initial division by car ownership level (e.g., Cain and Jones 2007).…”
mentioning
confidence: 99%